Estudio de la Tecnología Streaming en redes dual stack IPV4/IPV6 para la transmisión multimedia - Lavalle Diestre, Jaen Carlo Rodrigo (2017)
This document describes the procedures used for the simulation of the transmission streaming on a dual stack network for study and demonstrate both its feasibility as an IPv4 network and an IPv6 network and taking into account that the routing ipv4 and has ended and therefore opt for a transition to IPv6. which should ensure compatibility of different network applications.